2016
DOI: 10.1186/s12882-016-0332-5
|View full text |Cite
|
Sign up to set email alerts
|

An association between time-varying serum albumin level and the mortality rate in maintenance haemodialysis patients: a five-year clinical cohort study

Abstract: BackgroundUntil now, no long-term studies relating serum albumin level to mortality rate in prevalent haemodialysis (HD) patients have been conducted. We aimed to examine the association between serum albumin level and mortality over a 5-year period.MethodsThis study included 781 patients who received maintenance HD in a large, hospital-facilitated HD centre. Five-year medical records (2009–2013) were retrospectively reviewed, and the cut-off level for serum albumin level was set at 3.5 g/dL. The analysed albu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…Initially, the exercise and control groups did not show a significant difference with regard to qualitative and quantitative variables as well as muscle capacity and albumin levels. Almost half of the patients in this study had albumin levels lower than 4 g/dL and for each 0.1 g/dL of albumin lower than 4 g/dL, the mortality rate significantly increased (18,19). As for their muscle capacity, most of the patient's grip strength was lower than normal standards.…”
Section: Discussionmentioning
confidence: 70%
“…Initially, the exercise and control groups did not show a significant difference with regard to qualitative and quantitative variables as well as muscle capacity and albumin levels. Almost half of the patients in this study had albumin levels lower than 4 g/dL and for each 0.1 g/dL of albumin lower than 4 g/dL, the mortality rate significantly increased (18,19). As for their muscle capacity, most of the patient's grip strength was lower than normal standards.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, the overlapping clinical factors in the interaction models, DM, age, and albumin levels, and CT ratio, were associated with mortality in CKD, which has been reported by several studies. 26 30 …”
Section: Discussionmentioning
confidence: 99%
“…In large observational studies, strongest association with reduced mortality was seen in groups having serum albumin ≥ 40g/L [7,11]. Lower serum albumin levels have also been associated with peripheral vascular disease, chronic obstructive pulmonary disease, cancer and patients using temporary catheters [12].…”
Section: Discussionmentioning
confidence: 99%
“…Despite improvements in dialysis technology, the mortality rates remain high in the dialysis population compared to the age-matched general population [3]. Large observational studies have identified short HSD, high ultrafiltration rates (UFR) and high intradialytic weight gain (IDWG) as important independent markers of mortality and adverse cardiovascular outcomes [4-7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation